Radio spot on moringa (Moringa oleifera): Capsule radio sur le moringa (Moringa oleifera) - Sana, Halizata; Borelli, Teresa (2023)
Part of a larger information campaign on neglected and underutilized species (NUS), this radio program uses simple, colloquial language and daily life settings to promote NUS that were once common on farms and in the diets of people living in Burkina Faso and Niger. The radio campaign aims to promote local nutritious crops, which can be included in sustainable, climate-smart agriculture as well as become potential sources of income.